Saddle coronary embolism precipitates flash pulmonary edema. (2020) - Ahmad, Ali; Kusz, Halina; Khan, Hafiz; Isa, Sakiru
Abstract: Coronary artery embolism is as an infrequent but important cause of acute myocardial infarction. We present a rare case of a large saddle embolism in the coronary vasculature which led to an acute myocardial infarction and consequently flash pulmonary edema. Despite intensive medical management, our patient did not survive.